Manajemen Kurikulum Tahfizh Qur’an Juz 30 Di Lembaga Pendidikan Anak Usia Dini - Istiqomah, Siti (UIN Sultan Maulana Hasanudin Banten, 2024)
Nowadays memorizing the Qur'an has become a common phenomenon among early childhood. Many early childhood children are able to memorize the Qur'an even up to 30 juz. However, in its implementation, several problems were found that became obstacles in the process of memorizing the Qur'an. Therefore, it is necessary to have a tahfizh curriculum management in learning. The purpose of this study was to determine how the tahfizh curriculum management is in KB-TK Tahfizh Ar-Rasheed Bintaro. The research method used in this study is qualitative. Data sources were obtained directly from the school, namely the tahfizh teacher and the principal. The results of this study indicate that the implementation of the tahfizh curriculum management in KB-TK Tahfizh Ar-Rasheed Bintaro is running well, starting from curriculum planning, organizing, implementing, and controlling. Memorization achievements are made per class level, although in the first year the target has not all been achieved, but when in the final year the target of 30 juz can be completed. This is evidence of good tahfizh curriculum management.